A clinico-haematological study of hereditary hemoglobinopathies: a tertiary care centre experience - Atla, Bhagyalakshmi; Botta, Venkata Satya Kartheek; Balakrishnan, Padmapriya; Lalam, Neelima; Argi, Anuradha; Natukula, Kirmani (International Journal of Research in Medical Sciences, 2021)
Background: Hemoglobinopathies are the cause of concern in India for not only its effect on the quality of life in patients but also for their inheritance patterns. Tribal population of Visakhapatnam district has a high chance of inheriting hemoglobinopathies due to their culture of consanguineous marriage. Aim and objectives of current study were to know the distribution of various abnormal haemoglobins in cases with clinical suspicion of hemoglobinopathies. Methods: This hospital-based observational study was conducted for a period of 10 months in the department of pathology, Andhra Medical College, Visakhapatnam. A total of 151 cases with suspected hemoglobinopathies, their parents, and siblings were screened for the presence of hemoglobinopathies. 3ml of venous blood was collected to perform complete blood count, peripheral smear, reticulocyte count, sickling test and High Performance liquid chromatography (HPLC). Results: In the present study, out of 151 cases, 55 cases (36.42%) were adults, and 96 cases (63.57%) cases were children. 67cases (44.37%) were asymptomatic and 84 (55.62%) were symptomatic. The most common symptom of subjects are fever (23 cases, 27.38%) and dyspnoea (22 cases, 26.19%). 85 cases (56.29%) had normal HPLC, and 66 cases (43.70%) had abnormal hemoglobin variants. The most common hemoglobinopathy detected by HPLC was sickle cell trait (36 cases, 23.84%) followed by homozygous sickle cell anemia 15 (9.93%). Other hemoglobinopathies detected were beta-thalassemia trait; 8 cases (5.29%) and compound heterozygous sickle beta-thalassemia 3 cases (1.98%). Conclusions: Endemic areas for hemoglobinopathies has to be screened with HPLC along with complete hemogram in suspicious cases for the better diagnosis and management of the condition.